2009
DOI: 10.1002/bem.20541
|View full text |Cite
|
Sign up to set email alerts
|

Comparing performances of logistic regression and neural networks for predicting melatonin excretion patterns in the rat exposed to ELF magnetic fields

Abstract: Various studies have been reported on the bioeffects of magnetic field exposure; however, no consensus or guideline is available for experimental designs relating to exposure conditions as yet. In this study, logistic regression (LR) and artificial neural networks (ANNs) were used in order to analyze and predict the melatonin excretion patterns in the rat exposed to extremely low frequency magnetic fields (ELF-MF). Subsequently, on a database containing 33 experiments, performances of LR and ANNs were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Furthermore, there are studies with relatively small samples where data mining techniques, like SVM and Neural Networks have been used with high accuracy in classification problems [see e.g. [58,64-66]]. Equivalent or even superior performances have been reported for Linear Discriminant Analysis and Random Forests when compared with Neural Networks, Classification Trees and Support Vector Machines [see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are studies with relatively small samples where data mining techniques, like SVM and Neural Networks have been used with high accuracy in classification problems [see e.g. [58,64-66]]. Equivalent or even superior performances have been reported for Linear Discriminant Analysis and Random Forests when compared with Neural Networks, Classification Trees and Support Vector Machines [see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation could be observed between ELF MF polarization and the nature of the findings (positive vs. negative), the lowest effective intensity (1.4 μT) being reported for circularly polarized fields (cf. Jahandideh et al ., ). Two studies that compared rats of different ages found an effect that was more pronounced in younger than in older rats (Selmaoui and Touitou, , ).…”
Section: Elf Mf and Mlt Secretionmentioning
confidence: 99%
“…In rats, 22 studies were short term (≤ 2 weeks), 18 of them having been negative (review in Jahandideh et al, 2010;Swerdlow et al, 2006). And out of the seven studies that examined exposure of ≥ 4 weeks of duration to intensities > 1 mT, six have reported positive findings.…”
Section: Elf Mf and Mlt Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical studies associated with ELF include effects on gene expression [Lupke et al, 2006], calcium signaling [Blackman et al, 1982;McCreary et al, 2006], enzymatic activity [Di Loreto et al, 2009;Ravera et al, 2010], growth factor receptors [Ke et al, 2008;Sun et al, 2008], melatonin synthesis [Jahandideh et al, 2010] and events involving generation of free radicals [Simko, 2007]. ELF effects on cell proliferation have been described and both inhibition and stimulation has been observed, depending on cell type and exposure conditions [Olsson et al, 2001;Strasak et al, 2002;Verheyen et al, 2003].…”
Section: Introductionmentioning
confidence: 97%